Corporate Governance, Management Environmental Training, and Carbon Performance: The UK Evidence - Saleh F.A. Khatib (17788505) (2023)
Following the stress on corporate governance (CG) attributes and their roles on environmental performance, an investigation on the association between CG and carbon performance of the firms listed on the London Stock Exchange is conducted, using data of non-financial companies for the period from 2016 to 2020. To enhance the depth of analysis, this paper introduces management environmental training as a moderator, offering a more nuanced examination of the CG-carbon performance relationship. The findings showed that CG and environmental governance contribute to mitigating CO2 emissions, including the aggregate, Scope 2, and Scope 1 indicators. This suggests that companies prioritizing effective governance mechanisms are more likely to achieve comprehensive emissions management. Also, our results suggest that management environmental training has a moderating impact on the CG-CO2 emissions association, indicating that environment-related training of firm management enhances the efficiency of CG in dealing with environmental issues. The results have substantial implications for policymakers, regulators, and practitioners about the efficiency of CG mechanisms and environmental training in determining company environmental behaviour. Other Information Published in: Journal of the Knowledge Economy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13132-023-01650-w